An optimization model for cyclic scheduling problem in flexible robotic cells - Nejad, Mazyar Ghadiri; Kovacs, Gergely; Vizvari, Bela; Barenji, Reza Vatankhah (Springer London Ltd, 2018)
This study deals with scheduling problem of a flexible robotic cell with m-machines and a robot. The machines are identical, and each machine performs all of the processes for producing a finished product. These machines are arranged in a line where one input buffer and one buffer are put at the beginning and the end of the line, respectively. A robot transports parts between the machines and the input and output buffers. In this cell, each machine processes one part in each cycle. Since the cycle time depends on the order of the activities of the robot, for minimizing the cycle time, the order of the activities of the robot should be determined. A universal scheduling model of the problem is developed, and its reduced version is provided, excluding waiting time variables. Furthermore, a new model is proposed for maximizing the minimum robot return time to the machines in a cycle. The developed models numerically examined based on obtained products order from the reduced model for the cell with up to six machines. Moreover, the assignment problem method is used for determining lower bond results of the developed model and/or the optimal results (i.e., in case the operation times of the machines are small enough and the robot waiting time is zero). The results indicate that the reduced version of the model is significantly more efficient compared to the model of the literature.
Keywords: Flexible robotic cell; CNC machines; Robotic cell; Cyclic scheduling